Geochemistry of tephra from sediment core IZN19-15 from Lake Iznik (NW Turkey) - Renaldo Gastineau; Pierre Sabatier; Stefano C Fabbri; Flavio S Anselmetti; Patricia A Roeser; Nathaniel Findling; Fabien Arnaud; Mustafa Şahin; Serkan Gündüz; Sven-Oliver Franz; Julia De Sigoyer (PANGAEA, 2021)
The occurrence of previously geochemically identified tephra allowed refinement of the age-depth model by comparison with previously established volcanic eruption history (Roeser et al., 2012). Tephra layers were polished on thin sections and the glass shards were geochemically characterized using a JEOL JXA-8230 Electron Probe X-ray Micro Analyzer (EMPA; ISTerre Laboratory, University Grenoble Alpes) equipped with 5 wavelength dispersive spectrometers (WDS) and one energy dispersive spectrometer (EDS) detector. The measurements used the following conditions: 15 kV voltage, 2 nA beam current, and 5 to 7 μm beam size. For standardization, MPI-DING glasses (StHs6/80-G, GOR132-G) (http://georem.mpch-mainz.gwdg.de; Jochum et al., 2000), natural minerals, and synthetic oxides were used. Two glasses, Atho-G (http://georem.mpch-mainz.gwdg.de; Jochum et al., 2000) and KE-12 (Metrich & Rutherford, 1992), were analyzed together with the samples to verify analytical accuracy and to exclude the loss of alkalis. Analyses of glass shards yielding a total oxide sum less than 96% or suggesting mineral impurities were not included in this study. Analytical data were normalized to 100% total oxide values to enable comparison.
In: Gastineau, R et al. (2021): Sedimentary and geochemical analyses from 14 sediment cores of Lake Iznik, NW Turkey [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.935167